Different Routes for Conifer- and Sinapaldehyde and Higher Saccharification upon Deficiency in the Dehydrogenase CAD1 . Issue 3 (6th September 2017) - Van Acker, Rebecca; Déjardin, Annabelle; Desmet, Sandrien; Hoengenaert, Lennart; Vanholme, Ruben; Morreel, Kris; Laurans, Françoise; Kim, Hoon; Santoro, Nicholas; Foster, Cliff; Goeminne, Geert; Légée, Frédéric; et al.
Abstract : Down-regulation of CAD1 in poplar leads to different metabolic routes for coniferaldehyde and sinapaldehyde and alters lignin amount and structure, improving the physicochemical properties of wood for saccharification. Abstract: In the search for renewable energy sources, genetic engineering is a promising strategy to improve plant cell wall composition for biofuel and bioproducts generation. Lignin is a major factor determining saccharification efficiency and, therefore, is a prime target to engineer. Here, lignin content and composition were modified in poplar ( Populus tremula × Populus alba ) by specifically down-regulating CINNAMYL ALCOHOL DEHYDROGENASE1 ( CAD1 ) by a hairpin-RNA-mediated silencing approach, which resulted in only 5% residual CAD1 transcript abundance. These transgenic lines showed no biomass penalty despite a 10% reduction in Klason lignin content and severe shifts in lignin composition. Nuclear magnetic resonance spectroscopy and thioacidolysis revealed a strong increase (up to 20-fold) in sinapaldehyde incorporation into lignin, whereas coniferaldehyde was not increased markedly. Accordingly, ultra-high-performance liquid chromatography-mass spectrometry-based phenolic profiling revealed a more than 24, 000-fold accumulation of a newly identified compound made from 8-8 coupling of two sinapaldehyde radicals. However, no additional cinnamaldehyde coupling products could be detected in the CAD1-deficient poplars. Instead, the transgenic lines accumulated a range of hydroxycinnamate-derived metabolites, of which the most prominent accumulation (over 8, 500-fold) was observed for a compound that was identified by purification and nuclear magnetic resonance as syringyl lactic acid hexoside. Our data suggest that, upon down-regulation of CAD1, coniferaldehyde is converted into ferulic acid and derivatives, whereas sinapaldehyde is either oxidatively coupled into S′(8-8)S′ and lignin or converted to sinapic acid and derivatives. The most prominent sink of the increased flux to hydroxycinnamates is syringyl lactic acid hexoside. Furthermore, low-extent saccharification assays, under different pretreatment conditions, showed strongly increased glucose (up to +81%) and xylose (up to +153%) release, suggesting that down-regulating CAD1 is a promising strategy for improving lignocellulosic biomass for the sugar platform industry.